PENCEGAHAN STUNTING PADA SISWA MADRASAH IBTIDAIYAAH NURUL MAGFIRAH KENDARI DENGANPEMBERIAN OBAT PENCEGAHAN MASSAL (POPM) - Jabbar, Asriullah; Nasrudin, Nasrudin; Halik, Halik; Wahyuni, Wahyuni; Malik, Fadhliyah; Akib, Nur Illiyyin; Suryani, Suryani; Solo, Dian Munasari; Sida, Nurramadhani A.; Mubarak, Mubarak; Y, Muhammad Ilyas (LPPM Institut Pendidikan Nusantara Global, 2024)
Helminthiasis is a health problem that affects many children, especially elementary school. Helminthiasis can cause malnutrition because all nutrients are absorbed by worms, which will disrupt the mental and physical development of children, make children easily sick due to a decrease in their immune system, stunting or physical children become shorter and smaller than their peers, reduce children's intelligence and in some cases can also cause death in children. The purpose of this community service is the prevention and control of helminthiasis infection through the provision of mass preventive medicine for helminthiasis to prevent stunting in elementary school at Madrasah Ibtidaiyaah Nurul Magfirah Kendari. The method used, namely providing material about helminthiasis accompanied by giving deworming drugs to students. This service is in collaboration with the Health Team of Puskesmas Lepo Lepo Kendari.